Structure–property relationships in (1 − x)BaTiO3–xBiGdO3 ceramics. Issue 9 (September 2015) - Schileo, Giorgio; Feteira, Antonio; Reichmann, Klaus; Li, Ming; Sinclair, Derek C.
Abstract (1 − x)BaTiO3–xBiGdO3 ceramics were prepared by the solid state reaction method. X-ray diffraction and Raman spectroscopy indicate a maximum co-solubility of Bi/Gd in BaTiO3 at x = 0.10 with a change of symmetry from tetragonal to pseudo-cubic at x = 0.08. Backscattered electron images, however, reveal the presence of a secondary phase in x ≥ 0.06. The dielectric behaviour evolves continuously with x from a classical ferroelectric to a typical relaxor and this transition is accompanied by a shift in the permittivity maxima towards lower temperatures. The presence of two dielectric anomalies for x ≥ 0.06 is associated with residual core–shell structures, as revealed by transmission electron microscopy. The dielectric anomaly associated with the core regions remains at ∼120 °C, whereas the other anomaly decreases continuously towards lower temperature with x. This study shows that chemical equilibrium is much more difficult to achieve than in other (1 − x)BaTiO3–xBi[Me]O3 systems, where Me is Yb or Sc.